Medium temperature application of concentrated solar thermal technology: Indian perspective. (September 2017) - Naik, Hardik; Baredar, Prashant; Kumar, Anil
Abstract: Solar energy which is incident on the earth surface is mostly in diffused form. Hence, ordinary solar water heating technology is able to supply only low-temperature hot water (40–70 °C), primarily used for residential water and space heating. This range of temperature can hardly meet specific energy demand such as food processes, dairy processes and other industrial process heat requirement. Hence to utilize this diffused form of solar energy efficiently for heating in domestic or industrial applications, solar concentrators have to be used for generating temperatures in the range of 80–250 °C. The medium temperature applications can vary from domestic like cooking, boiling or dairy processes etc. to industrial like heat treatment, sterilizing, dyeing etc. This paper illustrates design and development of various concentrating solar thermal technologies along with its application in Indian market. The paper briefly reviews the need of such technologies; potential markets; and barriers and recommendations for deployment of available concentrated solar thermal technologies used for generation of medium temperature (80–250 °C). The paper focuses on the cases of successful implementation of the technology all over the country and also the government efforts to promote its use further for making it a cheaper and an alternative source of energy to fossil fuels for heating applications.